Capacitively Coupled Hybrid Ion Gel and Carbon Nanotube Thin‐Film Transistors for Low Voltage Flexible Logic Circuits. (25th June 2018) - Choi, Yongsuk; Kang, Joohoon; Secor, Ethan B.; Sun, Jia; Kim, Hyoungjun; Lim, Jung Ah; Kang, Moon Sung; Hersam, Mark C.; Cho, Jeong Ho
Abstract: The lamination of a high‐capacitance ion gel dielectric layer onto semiconducting carbon nanotube (CNT) thin‐film transistors (TFTs) that are bottom‐gated with a low‐capacitance polymer dielectric layer drastically reduces the operating voltage of the devices resulting from the capacitive coupling effect between the two dielectric layers sandwiching the CNT channel. As the CNT channel has a network structure, only a compact area of ion gel is required to make the capacitive coupling effect viable, unlike the planar channels of previously reported transistors that required a substantially larger area of ion gel dielectric layer to induce the coupling effect. The capacitively coupled CNT TFTs possess superlative electrical characteristics such as high carrier mobilities (42.0 cm 2 (Vs) −1 for holes and 59.1 cm 2 (Vs) −1 for electrons), steep subthreshold swings (160 mV dec −1 for holes and 100 mV dec −1 for electrons), and low gate leakage currents (<1 nA). These devices can be further integrated to form complex logic circuits on flexible substrates with high mechanical resilience. The layered geometry of the device coupled with scalable solution‐based fabrication has significant potential for large‐scale flexible electronics. Abstract : Capacitively coupled carbon nanotube (CNT) thin‐film transistors (TFTs) are developed by utilizing a crosslinked poly‐4‐vinylphenol/ion gel hybrid capacitive structure on a flexible substrate . The devices show excellent electrical characteristics including high mobilities (> 40 cm 2 (Vs) ‐1, high on/off ratios (> 10 3 ), and low subthreshold swings (< 200 mV dec ‐1 ) at low voltages below 3 V.